Analisis Daya Dukung Pondasi Tiang Bersirip Pada Tanah Lunak Dengan Variasi Jarak Dan Panjang Sirip - Julperizal Julperizal; Ferry Fatnanta; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Soft soil is a soil that has low shear strength. A construction which is built on soft soil usually faces some problems such as low bearing capacity and settlement. Pile foundation is used when a supported soil is located quite far from the surface so that the bearing capacity which can sustain the building has to rely on the skin friction. To obtain the higher pile bearing capacity, several modifications are made including the addition of fins on the pile. This research studies the behavior of finned piles, particulary the relationship between bearing capacity and settlement. Piles were modelled with one and two pair of fins with variations of fin's lengths of 0.50D, 0.75D, 1.0D, and 1.25D. Those piles using the Constant Rate of Penetration (CRP) method. The distances between fins also varies from 3D, 5D, to 7D. The interpretation of loading test data using the Terzaghi and Peck method then it was compared with empirical calculations using the Individual Bearing and Square Shear method.The loading test results show that the length and number of fins affect to bearing capacity of the pile. Piles with 1 (one) and 2 (two) fins are able to bearing greater loads than piles without fin. The largest pile bearing capacity occurs in pile models with fin length's of 1.25D and distance of 5D. The calculation which used the Individual Bearing method produces the value of bearing capacity which is relatively same to the Square Share method. The piles bearing capacity of the model test result is significantly different from the second calculation of the empirical method. The addition of the fins length is more dominant and it improves the piles bearing capacity if it is compared to the change of the distance between the fins.Keywords : Individual Bearing, length of fin pile, Spacing of Fin pile, Square shear